Honeybees of Asia editors. - Hepburn, H. R.; Radloff, S. E. (Sarah E.) 1948-.; SpringerLink (Online service). (Berlin New York Springer, 2011)
A multi-authored work on the basic biology of Asian honeybees, written by expert specialists in the field, this book highlights phylogeny, classification, mitochondrial and nuclear DNA, biogeography, genetics, physiology, pheromones, nesting, self-assembly processes, swarming, migration and absconding, reproduction, ecology, foraging and flight, dance languages, pollination, diseases/pests, colony defensiveness and natural enemies, honeybee mites, and interspecific interactions. Comprehensively covering the widely dispersed literature published in European as well as Asian-language journals and books, Honeybees of Asia provides an essential foundation for future research.
The Asian species of Apis / Sarah E. Radloff, H.R. Hepburn, and Michael S. Engel -- Phylogeny of the genus Apis /Nikolaus Koeniger, Gudrun Koeniger, and Deborah Smith -- Biogeography / H.R. Hepburn and Sarah E. Radloff -- Asian honeybees and mitochondrial DNA / Deborah R. Smith -- Genetic considerations / Catherine L. Sole and Christian W.W. Pirk -- Biology of nesting / Mananya Phiancharoen, Orawan Duangphakdee, and H.R. Hepburn -- Absconding, migration and swarming / H.R. Hepburn -- Comparative reproductive biology of honeybees / Gudrun Koeniger, Nikolaus Koeniger, and Mananya Phiancharoen -- Pheromones / Christian W.W. Pirk, Catherine L. Sole, and R.M. Crewe -- Honeybees in natural ecosystems / Richard T. Corlett -- The pollination role of honeybees -- Uma Partap -- Foraging / D.P. Abrol -- Energetic aspects of flight / H.R. Hepburn, Christian W.W. Pirk, and Sarah E. Radloff -- The dance language / Orawan Duangphakdee, H.R. Hepburn, and Jürgen Tautz -- Diseases of Asian honeybees / Ingemar Fries -- Asian honeybee mites / Natapot Warrit and Chariya Lekprayoon -- Colony defence and natural enemies / Stefan Fuchs and Jürgen Tautz -- Self-assembly processes in honeybees : the phenomenon of shimmering / Gerald Kastberger, Frank Weihmann, and Thomas Hoetzl -- Interspecific interactions among Asian honeybees / Ming-Xian Yang ... [et al.] -- Bibliography of the Asian species of honeybees / H.R. Hepburn and Colleen Hepburn.
Electronic reproduction.
Keywords: Honeybee -- Asia; Apis (Insects) -- Asia; Electronic books